S-adenosyl-l-methionine antidepressant-like effects involve activation of 5-HT1A receptors - Sales, Amanda J.; Maciel, Izaque S.; Crestani, Carlos C. [UNESP]; Guimarães, Francisco S.; Joca, Sâmia RL. (Elsevier, 2023)
S-adenosyl-l-methionine (SAMe), a methyl donor, induces antidepressant effects in preclinical and clinical studies of depression. However, the mechanisms behind these effects have been poorly investigated. Since SAMe is involved in monoamine metabolism, this work aimed at 1) testing the effects induced by systemic treatment with SAMe in mice submitted to the forced swimming test (FST) and tail suspension test (TST); 2) investigating the involvement of serotonergic neurotransmission in the behavioral effects induced by SAMe. To do that, male Swiss mice received systemic injections (1 injection/day, 1 or 7 days) of imipramine (30 mg/kg), L-methionine (400, 800, 1600, and 3200 mg/kg), SAMe (10, 25, 50, 100, and 200 mg/kg), or vehicle (10 ml/kg) and were submitted to the FST or TST, 30 min after the last injection. The effect of SAMe (50 mg/kg) was further investigated in independent groups of male Swiss mice pretreated with p-chlorophenylalanine (PCPA, serotonin synthesis inhibitor, 150 mg/kg daily, 4 days) or with WAY100635 (5-HT1A receptor antagonist, 0.1 mg/kg, 1 injection). One independent group was submitted to the FST and euthanized immediately after for collection of brain samples for neurochemical analyses. Serotonin (5-HT) and noradrenaline (NA) levels were measured in the hippocampus (HPC) and prefrontal cortex (PFC). Furthermore, to investigate if the treatments used could induce any significant exploratory/motor effect which would interfere with the FST results, the animals were also submitted to the open field test (OFT). The administration of imipramine (30 mg/kg), L-methionine (400, 800, 1600, and 3200 mg/kg), and SAMe (10 and 50 mg/kg) reduced the immobility time in the FST, an effect blocked by pretreatment with PCPA and WAY100635. None of the treatments increased the locomotion in the OFT. In conclusion, our results suggest that the antidepressant-like effects induced by SAMe treatment are dependent on serotonin synthesis and 5-HT1A receptor activation.
Keywords: 5-HT; 5-HT1A; Depression; S-adenosyl-l-methionine; SAMe; Serotonin; Stress